Optimization of Large Scale Produced Hard Carbon Performance in Na-Ion Batteries: Effect of Precursor, Temperature and Processing Conditions. Issue 16 (1st January 2018) - Irisarri, E.; Amini, N.; Tennison, S.; Ghimbeu, C. Matei; Gorka, J.; Vix-Guterl, C.; Ponrouch, A.; Palacin, M. R.
Abstract : Hard carbon materials were prepared from different precursors (phenolic resin and commercially available cellulose and lignin) under different pyrolysis and processing conditions using industrially adapted syntheses protocols. The study of their microstructural features enabled to assess that the nature of the precursor and the temperature of pyrolysis are the major factors determining the carbon yield and the surface area, the latter one having a major effect on the electrochemical capacity. Finally, the presence of surface groups and physisorbed water can also play a role both on the maximum reversible capacity achievable (by influencing the interaction of sodium ions with the hard carbon surface) and the irreversible capacity. Phenolic resin combining high carbon yield (∼50%), tap density (0.7 g⋅cm −3 ) and reversible capacity (249 mAh/g) was found to be the precursor producing the most suitable hard carbon for practical use in Na-ion batteries. Cellulose can be a good candidate as well, the lower carbon yield being counterbalanced by its lower price and higher capacity (280 mAh/g).